Znaczenie Chin w regionie Azji-Pacyfiku - Michalczyk, Joanna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Transformation of China's economy has influenced the situation not only in the Asia-Pacific region but even in the world. Dominative position of China is a result of reforms conducted by Deng Xiaoping. Thanks to them, many economic indicators have achieved high level and guaranteed China to appear among major countries in the world, such as USA, Japan or Russia. After China's accessing to the WTO, the connection between this country and other of Asia-Pacific region has become stronger. It concerns particularly flows of foreign direct investment and foreign trade. The results of China's economic liberalization gives it a strategic position for most of Asiatic countries, where China is the main importer of merchandise. It makes them dependent on China. The opening of China's economy brings many positive and negative results to some countries. Consequently, one of the most important purposes in every country's politics should be taking a new China's position into consideration that may help them to get good results from co-operation. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 211-226